Evaluasi Pelaksanaan Survei Lingkungan Belajar - Rahmatia Lang Ere; Irna K. S. Blegur (Universitas Nusa Cendana, 2021)
This research conducted to evaluate the implementation of the Learning Environment Survey for senior high school teachers in Indonesia which has been carried out in September and October 2021. This is a qualitative-research using in-depth interview techniques. Sources of data are seven teachers of MAN (a government Islamic school) in Alor island, Indonesia, who have filled out this survey in September and one proctor of the National Assessment of MAN Alor. Data analysis is caried out by looking for sub-themes, then determining the relationship between sub-themes to gain understanding. The results of the research are as follows: first, the teacher’s data which are used as the basis for determining the respondents to the survey is considered not valid enough. Secondly, several questions in the survey were considered too sensitive to be questioned because seems like to stir up the privacy of the education unit. The third, questions in this survey are considered too many, too long, and repeat the same sentence a lot